MEMBACA SIMBOL PANGGAL DALAM PERTUNJUKKAN ESTETIKA CACI ETNIK MANGGARAI DI FLORES - Karolus Budiman Jama (Jurnal Lazuardi, 2020)
The Caci aesthetic of the Manggarai ethnic group in Flores does not only function as a show that entertains the community. Caci aesthetics contributes to the value of knowledge for this aesthetic society. A number of aesthetic elements such as the call are symbols of the stored knowledge and record the traces of the Manggarai ethnic culture. Panggal is an aesthetic artifact, the fruit of the world of Manggarai ethnic aesthetic ideas and dialectic aesthetic knowledge. The hermeneutic theory of symbols is used to dissect research problems. This research uses qualitative research methods with an ethnographic approach. The findings in this study are that the pelvis is an aesthetic artifact that carves a fertility concept that can be read from two dimensional oppositions, namely the physical and the spiritual.